APPLICATION OF MUSYARAKAH MUTANAQISAH CONTRACT IN FINANCING AT BANK ACEH SHARI'AH - Faradilla, Riska; Khalidin, Bismi (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
The purpose of this article is to find out the form of the implementation of the Musyarakah Mutanaqisah contract at Bank Aceh Syari'ah and to find out the obstacles in the implementation of the contract by Bank Acerh Syari'ah. This research used a qualitative approach, which the primary data gathered from the interview, and focus group discussion. While the secondary data found from other related resources such as books, journal and other articles related to this topic. Ther rersurlt found that ther contract as a form of cooperation involving two or more parties, where each includes capital and share the results according to the agreement. Musyarakah financing offered by Bank Aceh Syariah provides capital support to customers, with risks and benefits shared based on the contribution of each party. The Bank faces various obstacles in the implementation of the contract in financing scheme, including customary dishonesty, low product demand, and public misunderstanding of the system. The Musyarakah Mutanaqisah agreement is implemented based on the Indonesia Ulama Council decision No.01/DSN-MUI/X/2013 concerning the implementation of the musyarakah mutanaqisah agreement in financing products which is an important step in regulating finance to operate in accordance with sharia principles, which aims to advance the community’s economy and implement Islamic sharia comprehensively.